1988
DOI: 10.2190/b561-n2d3-ndxe-eg9y
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Variables and Recreational Substance Use among College Students

Abstract: The purpose of this study was to examine the relationship between demographic variables and recreational substance use within the college population. Eight hundred thirty-two college-aged students were given the Wellness Activity Profile, a questionnake that includes sections yielding demographic and recreational substance usage data. Discriminant analyses of the data indicated that persons using recreational substances differed significantly from non-users. Marijuana users differed from non-users on parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The maximum likelihood estimates of / 3 are given in Table 4. Since there appears to be considerable doubt about the true model (Carlson & Davis, 1988;Forney et al, 1990), four different models are estimated, after imposing various zero restrictions on the ps in equation (4). Each model is estimated using data from both survey types and the parameter estimates are examined for robustness across survey type and model specification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum likelihood estimates of / 3 are given in Table 4. Since there appears to be considerable doubt about the true model (Carlson & Davis, 1988;Forney et al, 1990), four different models are estimated, after imposing various zero restrictions on the ps in equation (4). Each model is estimated using data from both survey types and the parameter estimates are examined for robustness across survey type and model specification.…”
Section: Resultsmentioning
confidence: 99%
“…5 .05) and a low LFU=.05. The goodness of fit measures can be compared to Carlson & Davis (1988) who fail to find any statistically significant covariates for cocaine use and Forney, et al (1990) who report a quite small coefficient of determination of .14 in stepwise regression estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The article also examines further the results of previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] which indicated that the use of any particular drug correlates with the concurrent or subsequent use of other drugs as part of the adolescent drug progression 7,[14][15][16] or propensity to use drugs. 10 This study is based on the results from the PRIDE (Parent Resources Institute for Drug Education) CANADA Drug Prevalence Questionnaire completed by 18,685 Grades 9 through 12 students in two Western Canadian provinces in the fall of 1995-96.…”
mentioning
confidence: 99%